2017
DOI: 10.1111/anec.12469
|View full text |Cite
|
Sign up to set email alerts
|

Impact of functional training on geometric indices and fractal correlation property of heart rate variability in postmenopausal women

Abstract: Were observed in the FTG: increased SD1 (CG 0.13 ± 4.00 vs. 3.60 ± 8.43), beat-to-beat global dispersion much greater as an increased in the dispersion of long-term RR intervals and increased fractal properties of short-term (α1) (CG -0.04 ± 0.13 vs. 0.07 ± 0.21). FT promoted a beneficial impact on cardiac autonomic modulation, characterized by increased parasympathetic activity and short-term fractal properties of the dynamics of the heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(53 citation statements)
references
References 47 publications
(102 reference statements)
0
53
0
Order By: Relevance
“…As already pointed out, this is a pioneer study, evaluating the cardiac autonomic modulation and cardiorespiratory parameters after functional training in postmenopausal women. Although, another study recently published the same functional training protocol that evaluated the influence of functional training on the geometric indexes of HRV and fractal correlation properties of the dynamics of HR in menopausal women . The authors of that study observed the increase in the index SD1 beat‐to‐beat global dispersion, in the dispersion of long‐term RR intervals (SD2) and in fractal properties of short‐term (α1) dynamics of the heart rate, when comparing the functional group with the control.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As already pointed out, this is a pioneer study, evaluating the cardiac autonomic modulation and cardiorespiratory parameters after functional training in postmenopausal women. Although, another study recently published the same functional training protocol that evaluated the influence of functional training on the geometric indexes of HRV and fractal correlation properties of the dynamics of HR in menopausal women . The authors of that study observed the increase in the index SD1 beat‐to‐beat global dispersion, in the dispersion of long‐term RR intervals (SD2) and in fractal properties of short‐term (α1) dynamics of the heart rate, when comparing the functional group with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for this study included: no menstruation for >12 months; having follicle stimulating hormone level >30 mIU/mL; not presenting known health problems (such cardiovascular, respiratory, metabolic, neurological or orthopedic disorders) or limitations that might prevent carrying out the proposed exercise; not having practiced any regular physical activity or weight training in the 6 months before the beginning of the clinical trial; non‐smokers and who did not drink alcohol often; and providing a medical certificate that would allow them to practice physical exercises, making all review proposals and signing the consent form.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations